Anti-inflammatory activity of Alchornea triplinervia ethyl acetate fraction: Inhibition of H2O2, NO and TNF-alpha - Mascia Lopes, Flavia Cristine [UNESP]; Calvo, Tamara Regina [UNESP]; Vilegas, Wagner [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Informa Healthcare, 2010)
Context: Alchornea triplinervia (Spreng.) Mull. Arg. (Euphorbiaceae) is a tree widespread in many Brazilian states. This plant naturally occurs in different ecosystems including tropical Atlantic forest, Amazon rain forest, moist tropical mixed forest, savanna forest, among others. Local populations traditionally use it in tea form to treat gastric disturbances.Objective: The objective of this research was to evaluate the plant A. triplinervia as a potential inhibitor of some macrophage functions involved in the inflammatory process.Materials and methods: The effects of Alchornea triplinervia ethyl acetate fraction (AtF) on hydrogen peroxide (H2O2), nitric oxide (NO) and tumor necrosis factor-alpha (TNF-alpha) production in peritoneal macrophages were investigated using phenol red, Griess reagent and a sandwich immunoassay, respectively.Results: AtF chromatographic analyses indicate the presence of flavonoids as majority compounds. The fraction also showed an intense inhibition of H2O2 and NO production. The inhibitory effects of the fraction in H2O2 and NO production ranged from 72.25 +/- 4.68 to 69.64 +/- 4.21 and from 47.8 +/- 8.96 to 76.77 +/- 8.11%, respectively in the two tested concentrations, 15.62 and 62.5 mu g/mL. TNF-alpha production was partially inhibited in the tested concentrations and the inhibitory rate was around 18%.Discussion and conclusion: It is supposed that the elevated biological potential of A. triplinervia is related to the presence of phenolic compounds in the plant leaves. According to the results observed in this study, it is suggested that AtF presents anti-inflammatory activity, supporting the traditional use of A. triplinervia in Brazilian folk medicine.
Keywords: Biological activities; immune system; inflammation; medicinal plant